PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Kuriah, Hanik Lailatul; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test the influence of the characteristic of the company and the corporate social responsibility to the aggressiveness tax of a company. Characteristic of the company uses firm size, leverage, and capital intensity. The population of this research is the entire manufacturing companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been done by using purposive sampling and 25 companies have been obtained as sample criteria during 2010-2014. The hypothesis test has been done by using multiple linear regressions analysis technique. The result of this research shows that firm size and leverage have significant influence to the tax aggressiveness; it means that the size of a company will influence the tax aggressiveness level in each company. Leverage uses debt to minimize tax burden of companies even more likely to lead aggressively against the corporation tax. Meanwhile, capital intensity does not have any influence to the tax aggressiveness, it means the company is not accidentally save a large proportion of assets for tax evasion, but the company uses fixed asset for the operational objectives of the company. CSR has significant but negative influence to the tax aggressiveness, it means that the company applies CSR costs for the benefit of society and the company does not on purpose to conduct tax aggressiveness through the costs which has been spent for CSR program.Keywords: Characteristics of the Company, Corporate Social Responsibility, Tax aggressiveness, Effective Tax Rate, Tax Avoidance.